Exploitation of platelets for antitumor drug delivery and modulation of the tumor immune microenvironment - Jie Guo; Meng-Fei Wang; Yong Zhu; Fumio Watari; Yong-Hong Xu; Xiao Chen (Compuscript Ltd, 2023)
Platelets are blood components traditionally believed to have fundamental roles in vascular hemostasis and thrombosis. In recent years, platelets have received new attention for their roles in tumorigenesis and progression. On the one hand, platelets are actively recruited by various tumors and comprise a crucial part of the tumor microenvironment (TME), thus inspiring the use of platelets for tumor-targeted drug delivery. To this end, various platelet-based devices have been proposed, such as natural platelets, engineered platelets, platelet membranes, and platelet-derived microparticles. On the other hand, platelets are involved in tumor immunosuppression mechanisms, by directing and/or assisting various tumor-associated immune cells. However, in the context of inflammation and autoimmune diseases, platelets can amplify immune responses by promoting immune cell mobilization and activation, thereby exacerbating tissue damage. Thus, interest is growing in the use of tumor-associated platelets as targets for therapeutic modulation of the TME and augmenting anti-tumor immune responses. In this review, we summarize current advances in exploiting platelets for both antitumor drug delivery and immune modulation of the TME.